Reviewing Feminine and Masculine Words in the Effects of Anima and Animus in the Jalal Al Ahmad and Simin Daneshvar Fiction - Abdollah Hasanzadeh Mirali; Sepideh Rahmati Afrapoli; Hasan Akbari Beyragh; Yadallah Shokri (مطالعات زبانی و بلاغی)
The issue of gender connection and language and the language specific to each gender is known as linguistic behavior in the topics of grammar, terminology, meaning, and conceptualization.The interests and habits and intellectual, linguistic and verbal tendencies of both men and women show that the topic of female and male is important in the presence and extent of using vocabulary for each gender.The culture of the society has determined the language and the way of speaking and the choice of words for each gender.Part of the topic of female and male archetypes of anima and animus is revealed in the context of language, text and linguistic behaviors.This research will investigate the gender signs of feminine and masculine words in the anima and animus aspects of the text of the stories by the descriptive-analytical method and the library study tool. In order to understand the connection between linguistics and psychological criticism with the literary types of stories and novels, it is necessary to conduct comparative-analytical studies. In this research, the results have shown that the realistic style and the reflection of the society's culture and the spirit of the nation in the stories of Al-Ahmed and Daneshvar have caused the expression of anima and animus in the language of the characters to be less. These two authors do not show such unusual contradictions in the society of that period.The prominent elements and components of feminine and masculine words in the manifestations of anima and animus in the works of Jalal Al Ahmad and Simin Daneshvar are:Emotional, romantic and caressing words, abusive and harsh words and sentences in women's speech, color words, children's words, adjectives for women or men, words related to the roles of women and men in the family and society, language related to communicating with the opposite sex, words that specific to the appearance of women or men, interrogative words and formal, standard and popular words and Feminine and masculine words superior and inferior.